Current and future perspectives on pregnancy and lactation-associated osteoporosis - Gak, Nataliya; Abbara, Ali; Dhillo, Waljit S.; Keen, Richard; Comninos, Alexander N. (Frontiers in Endocrinology, 2024)
Normal pregnancy and lactation have a marked physiological impact on maternal bone metabolism. This impact is usually temporary and reversible, but some women sustain fragility fractures whilst pregnant or lactating, termed pregnancy and lactation-associated osteoporosis (PLO). These fractures have severe negative consequences on their quality of life, at what is a crucial stage in a mother's life.Identifiable risk factors include a low body mass index (BMI), reduced physical activity during adolescence, a strong family history of osteoporosis, and genetic variations in the LRP5 and WNT1 genes. However, due to the rarity of PLO and the limited awareness surrounding it, there has been slow progress in understanding its pathophysiology and identifying the most effective treatments. Indeed, the data available primarily originates from observational and case studies, resulting in little clear guidance on a comprehensive and multidisciplinary approach. This mini-review synthesises the latest data on incidence, pathophysiology, and management in PLO, providing current and future perspectives and highlights the need for evidence-based guidelines to improve both short-term and long-term outcomes for women with PLO.